Teresa y Luis, Luis y Teresa. Dos santos en tiempos recios. - CALLADO ESTELA, EMILIO (Scripta, 2016)
The present article analyses the relation between two big Spanish saints of the Catholic Counter-reformation, Teresa de Jesus and the Dominican monk Luis Bertrán